Bargaining in legislatures: A new donation paradox - Maria Montero (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
It is well known that proposers have an advantage in the canonical model of bargaining in legislatures: proposers are sure of being part of the coalition that forms, and, conditional on being in a coalition, a player receives more as a proposer than as a coalition partner. In this paper I show that, if parties differ in voting weight, it is possible for a party to donate part of its proposing probability to another party and be better-off as a result. This can happen even if the recipient never includes the donor in its proposals. Even though actually being the proposer is valuable, having a higher probability of being proposer may be harmful.
Keywords: C78; D72; 330; legislative bargaining; weighted majority games; voting paradoxes; Wahlverhalten; Gesetzgebung; Verhandlungsmacht; Spieltheorie